Handbook of Psychodiagnostic Testing Analysis of Personality in the Psychological Report - Kellerman, Henry; Burry, Anthony (Springer New York : Imprint: Springer, 2007)
Since the debut of the original edition, the Handbook of Psychodiagnostic Testing has been an invaluable aid to students and professionals performing psychological assessments. The new Fourth Edition continues in that tradition, taking the reader from client referral to finished report, demonstrating how to synthesize details of personality and pathology into a document that is focused, coherent, and clinically meaningful. As with the previous editions, authors Kellerman and Burry offer a systematic framework for choosing the most relevant material from seemingly overwhelming amounts of test data. Separate chapters offer clear rationales for each component of the report (e.g., cognitive functioning, interpersonal behavior, control mechanisms), and how they relate to one another. Helpful summaries follow each chapter, and tables and charts provide salient facts and findings at a glance. Features of the updated Fourth Edition: A clear blueprint for writing effective, clinically integrative psychological reports. Emerging areas of interest in testing, including ethnic and language issues. Guidelines for assessing strengths and potential as well as pathology. Review of current diagnostic nomenclature, with discussion of evolving DSM categories and recognized clinical entities outside the DSM system. Brand-new sections on the major standardized intelligence tests. Expanded chapter devoted to testing counselors, teachers and parents. Help for writing-anxiety: overcoming blocks, getting past role conflicts, resisting speculation, and more. The Handbook makes an elegant student resource by showing how reports can reflect not just the subject's individuality, but the tester's as well. All professionals who engage in psychological assessment will find it an invaluable resource as well.